Analysis of Scapular Kinematics and Muscle Activity by Use of Fine-Wire Electrodes During Shoulder Exercises. Issue 5 (April 2020) - Berckmans, Kelly; Castelein, Birgit; Borms, Dorien; Palmans, Tanneke; Parlevliet, Thierry; Cools, Ann
Background: During nonoperative or postoperative rehabilitation after sports injuries, exercise selection is often based on minimal load on the injured/repaired glenohumeral structures, while optimally activating scapulothoracic muscles. Previous research explored scapular muscle activity during rehabilitation exercises using surface electromyography (EMG). However, limited information exists about the deeper lying muscle activity, measured with fine-wire electrodes, even more in combination with 3-dimensional scapular kinematics. Purpose: To report scapular kinematics synchronously with surface and fine-wire EMG during specific shoulder exercises for early rehabilitation. Study Design: Descriptive laboratory study. Methods: A total of 23 healthy male patients were recruited. Three-dimensional scapular kinematics were measured combined with EMG recording of 8 muscles during 4 commonly used shoulder exercises (inferior glide, low row, lawnmower, and robbery). Upper (UT), middle (MT), and lower (LT) trapezius and serratus anterior muscle activities were measured with bipolar surface electrodes. Intramuscular electrodes were placed in the levator scapulae (LS), rhomboid major (RM), pectoralis minor (Pm), and infraspinatus (IS) muscles. All data were normalized as a percentage of maximal voluntary isometric contraction (%MVIC). A linear mixed model with Bonferroni correction was applied for statistical analysis. Results: Scapular kinematics revealed an anterior tilt position during the inferior glide, low row, and robbery ( P < .05). An upward rotation position between 20° and 30° was reached in all exercises except low row. Inferior glide (31°) and low row (42°) represented a significantly increased internal rotation position compared with lawnmower and robbery. Lawnmower and robbery showed significantly ( P < .05) more MT (lawnmower, 36% MVIC; robbery, 39% MVIC) and RM (lawnmower, 59% MVIC; robbery, 66% MVIC) activation compared with inferior glide and low row. Lawnmower and robbery showed significantly ( P < .05) less Pm activation (9.5%-12% MVIC). LS was significantly more active during robbery (58% MVIC) compared with inferior glide and low row (27%-36% MVIC) ( P < .05). IS showed moderate activity (24%-37% MVIC) for all exercises, except low row (13% MVIC). Conclusion/Clinical Relevance: This study provides new insights about scapular positions and activation of the deeper layer muscles during 4 commonly used shoulder rehabilitation exercises. The lawnmower showed a favorable position of the scapula with less Pm activity in contrast to the low row. The inferior glide, lawnmower, and robbery should not be implemented in early phases of shoulder rehabilitation because of their moderate muscle activity.